Предмет: Алгебра,
автор: ELexir
решите систему уравнений
2(x+y)^2 - 7(x+y) + 3 = 0,
2x-3y= -1
Ответы
Автор ответа:
0
пусть (x+y)=a, тогда:
2a^2-7a+3=0
D=49-24=25
a1=(7+5)/4=3 a2=(7-5)/4=0.5
a=3 или a=0.5
делаем обратную подстановку:
х+у=3 или х+у=0.5
Автор ответа:
0
(x+y-3)*(2x+2y-1)=0
2x-3y=-1
x+y-3=0
2x+2y-1=0
2x-3y=-1
1 случай:
x+y-3=0
2x-3y=-1
x=-y+3
2x-3y=-1
x=-y+3
2(-y+3)-3y=-1
x=-y+3
y=1,4
x=-1,4+3
y=1,4
x=1,6
y=1,4
2 случай:
2x+2y-1=0
2x-3y=-1
x=-2y+1 / 2
2x-3y=-1
x=-2y-1 / 2
2(-2y-1 / 2)-3y=-1
x=-2y-1 / 2
-2*2y-1 / 2 - 3y=-1
x=-2y-1 / 2
y=0,4
x=- 2*0,4-1 / 2
y=0,4
x=0,1
y=0,4
Окончательный ответ:
x=1,6
y=1,4
x=0,1
y=0,4
Похожие вопросы